Influência da administração de 1,25 vitamina D3 na inflamação intestinal crônica antígeno específica - Pedruzzi, Monique de Moraes Bitteti (2013)
BACKGROUND: Vitamin D (an immunomodulator nutrient) can contribute in the recovery of an inflamed intestinal mucosa, due to a deregulation of the immune response by negatively regulating of Th1/Th17 responses while favoring Th2/Th3 responses. HYPOTHESIS: The administration of 1,25 dihidroxicolicalciferol is able to modulate the course of an intestinal inflammatory response by decreasing the inflammatory process. OBJECTIVES: Evaluate local and systemic impacts of the administration of 1,25 dihidroxicolicalciferol, in the induction and maintenance of a chronic antigen specific gut inflammation in a mouse model established using an updated histomorfometric classification of the changes in the small intestine during intestinal inflammation. MATERIAL AND METHODS: C57BL/6 male mice were sensitized with two subcutaneous inoculations of peanut protein extract (16 groups (n=7) along with one group that only received saline), alum was only added in the primary inoculation. After sensitization, all groups were fed exclusively with peanuts for 30 days. The 15 sensitized groups were inoculated with a single dose of Vitamin D in the following moments: with the primary or booster inoculation or on the1st, 11th or 21st day of challenge diet with one of 3 doses (75, 150 or 300ng). The control groups (C(+) and C(-)) did not receive Vitamin D. Body weight, food consumption, serology, T cells phenotype from mesenteric lymph nodes (CD4+/CD8+/CD25+) and histomorphometry of the small intestine was assessed. To determine the significance (p<0.05) ANOVA with Tukey post-test or Sidak's was used. Approval in the ethics committee (CEPA) registration No 00101-09. RESULTS: The only dose and timing of Vitamin D administration that interfered with anti-peanut IgG titers was 300ng at sensitization increasing the titers. All other groups remained with similar antibody synthesis compared to C(+). However, all doses led to a partial recovery of the intestinal mucosa by reducing the degree of inflammation, different from the destructive lesion of C(+) group. The lowest dose of Vitamin D (75ng) was only effective when administered on day 21 of the challenge while oral doses of 150 and 300ng were efficient since the sensitization period. The most significant recovery was obtained with doses of 150ng on 21st day and 300ng in 11th and 21st days of oral challenge, however with no complete recovery was obtained within the trial period. The decrease in the intensity of the inflammatory response was accompanied by a concomitant increase of CD4+CD25+ and CD8+CD25+. As to the systemic repercussions groups that received 75ng concomitant to sensitization showed weight loss and decrease in consumption of peanuts while the groups that received this dose during oral challenge showed no changes in weight or food consumption. The higher doses (150 and 300ng) protected the animals from weight loss and decrease in the consumption of peanut at all times. CONCLUSIONS: Vitamin D shows a therapeutic effect by reducing the inflammatory response in a dose and time dependent manner with the best therapeutic results with higher doses. The histomorphometric classification proposed was effective in discriminating subclinical lesions in a murine model of intestinal inflammation